IMPACT OF THE PROFESSIONAL IMAGE OF THE LEADER ON THE DEVELOPMENT OF THE EDUCATIONAL INSTITUTION - Kovalchuk Vasyl (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2023)
This article provides a comprehensive review and analysis of scientific research on the role of the leader’s image in shaping the image of an educational institution and its positioning in society. The article aims to analyse the functions of the head of an educational institution and study the influence of their image on the development of the school, underlining the components of the school director’s image that influence its effectiveness in the educational labour market. It highlights the increasing competition faced by modern educational institutions, necessitating active demonstration of their effectiveness and rationalization of their existence. The quality of education and the achievements of graduates emerge as decisive factors in attracting the attention of parents and students. Educational institutions must adapt to pedagogical trends, integrate advanced technologies, and implement an individualized approach to learning. The interaction with the community and the formation of a positive school image are crucial. The director’s role is pivotal, with their leadership qualities and strategic planning influencing the perception of the school and shaping a positive impression of the entire institution. The article analyses the concept of “image” based on the studies of economist K. Boulding, who considered it a key to understanding society. It emphasizes that image is grounded in belief, unlike objective knowledge, and shapes behaviour based on the perception of the world. Theoretical frameworks proposed by S. Williams and M. Moffit introduce the concept of imaging as a two-way process involving the creation and consumption of an image, encompassing all communicative processes and their influences. Image consumption is categorized into levels of perception, comprehension, and evaluation, impacting the formation of perceptions and attitudes toward the image bearer. The article views image as a success factor in professional activities and competitiveness in the educational services market. It underscores the importance of image in the global information space and the need to specify the concept of “professional image” in the conditions of an information society. The article focuses on the significance of the organization’s image in the contemporary market environment and its influence on stability and longevity. It explores aspects of managerial image, professional image, and leader image. The structural components of the leader’s image include personal characteristics, social characteristics, and symbolic significance. A new direction, pedagogical imageology, aimed at forming the image of educators and educational institutions, is discussed. Universal functions of image encompass communicative, informational, cognitive, emotional, and other aspects, which are defining aspects of the impact of image on professional development and contributing to positive societal perception. The study analyses the Professional Standard “Head (Director) of General Secondary Education Institution”, outlining a list of job functions and professional competencies. The identified structural components of the school director’s professional image include expertise, leadership qualities, communication skills, ethics and integrity, innovativeness and strategic thinking, community interaction, and reputation. It has been concluded that to achieve stability and strategic development of the educational institution, the director must be not only an effective leader, but also a bearer of a positive image for the entire school community, education management, and the public.